Analysis of Hydrocyclone Geometry via Rapid Optimization Based on Computational Fluid Dynamics. Issue 9 (9th August 2021) - Liu, Lin; Zhao, Lixin; Reifsnyder, Samuel; Gao, Sheng; Jiang, Minzheng; Huang, Xueqiang; Jiang, Minghu; Liu, Yang; Rosso, Diego
Abstract: Hydrocyclones exploit density gradients for the centrifugal separation of dispersions in a continuous liquid. Selection of the geometrics for optimal separation is case specific, like the media characteristics. The existing optimization method based on computational fluid dynamics (CFD) provides a powerful analytical tool but requires long computational times. The most common praxis for CFD optimization is via the single‐factor optimization method (SFOM). In this study, a novel approach is presented as an improved rapid optimization method that implements a dynamic‐mesh and user‐defined function optimization method (DUOM). The DUOM adapts the dynamic‐mesh approach from other applications to the optimization analysis of hydrocyclones. The DUOM reduced the computational time by 31.1 %, compared to the SFOM. Abstract : A rapid computational fluid dynamics optimization method (DUOM) for hydrocyclone geometries is presented that can avoid the inevitable repeated modeling, meshing, and simulation steps in the optimization process of traditional methods. Exemplified by the vortex finder length of a hydrocyclone, the DUOM is shown to reduce the operating time of optimization by 31.1 %.